The Impact of Digital Marketing, Personal Selling, Sponsorship and Brand Image Towards Purchase Decision Wedding Organizer Client in Surabaya - Annora Shabhati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This research was conducted to determine the impact of Digital Marketing (X1), Personal Selling (X2), Sponsorship (X3), and Brand Image (X4) towards Purchase Decision(Y) of wedding organizer clients in Surabaya. This research used a quantitative method to analyze the effect between the independent and dependent variables. The sample was taken from purposive sampling consist of 100 wedding organizer clients in Surabaya who at least had used the service in the last two years. Questionnaire was used as the research instrument to collect the primary data. This research is also supported by secondary data from previous study to support the result. The data collected were analyzed using the SPSS application. The results of this research indicate that Digital Marketing (X1) and Personal selling (X2) have asignificant positive impact on Purchase Decision(Y). While the Sponsorship (X3) and Brand Image (X4) do not have significant positive impact on Purchase Decision (Y). Furthermore, Digital Marketing (X1), Personal Selling (X2), Sponsorship (X3), and Brand Image (X4) are indicated to have a significant positive impact simultaneously on Purchase Decision(Y).Keywords: Digital Marketing, Personal Selling, Sponsorship, Brand Image, Purchase Decision, Wedding Organizer